2001
DOI: 10.1002/1521-3765(20010903)7:17<3756::aid-chem3756>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

The Charge Density Distribution in a Model Compound of the Catalytic Triad in Serine Proteases

Abstract: Combined low temperature (28(1) K) X-ray and neutron diffraction measurements were carried out on the co-crystallised complex of betaine, imidazole, and picric acid (1). The experimental charge density was determined and compared with ab initio theoretical calculations at the B3LYP/6-311G(d,p) level of theory. The complex serves as a model for the active site in, for example, the serine protease class of enzymes, the so-called catalytic triad. The crystal contains three short strong N-H...O hydrogen bonds (HBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
53
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 75 publications
8
53
1
Order By: Relevance
“…Thus, it is shown that strong hydrogen bonding can indeed lead to the formation of relatively rigid linkers in a framework structure, resembling other CPs with NTE behavior. Furthermore, the study used source function calculations to show that this N‐H‐N hydrogen bond followed all the established hydrogen bond classifications developed for oxygen containing hydrogen bonds, especially the fact that the contribution from hydrogen and acceptor atom to the hydrogen bond BCP increases significantly with the covalency of the hydrogen bond (Figure ) . This purely density based descriptor even seems to be sensitive to the nature of the hydrogen vibration potential with significantly larger contributions from the hydrogen atom for LBHB than for asymmetric single‐well hydrogen bonds.…”
Section: Materials Classesmentioning
confidence: 94%
“…Thus, it is shown that strong hydrogen bonding can indeed lead to the formation of relatively rigid linkers in a framework structure, resembling other CPs with NTE behavior. Furthermore, the study used source function calculations to show that this N‐H‐N hydrogen bond followed all the established hydrogen bond classifications developed for oxygen containing hydrogen bonds, especially the fact that the contribution from hydrogen and acceptor atom to the hydrogen bond BCP increases significantly with the covalency of the hydrogen bond (Figure ) . This purely density based descriptor even seems to be sensitive to the nature of the hydrogen vibration potential with significantly larger contributions from the hydrogen atom for LBHB than for asymmetric single‐well hydrogen bonds.…”
Section: Materials Classesmentioning
confidence: 94%
“…Comparing the ADPs of the 33 heavy atoms in 1 by using the program UIJXN leads to a mean deviation ${\left\langle {\Delta U} \right\rangle }$ of 0.00058 Å 2 ,67 which, for such a large system, is an excellent correspondence compared with other X/N studies 68. The hydrogen nuclear positions and ADPs, which are important in accurate ED modeling of hydrogen‐bonded systems such as 1 ,69 were therefore expected to be of excellent quality. Increasing the complexity of the multipole model of the host structure, for example, by removing the center of symmetry, removing constraints (electronic, positional, and thermal), or adding additional radial expansion–contraction parameters did not result in a significant improvement of the residual density or the agreement factors.…”
Section: Methodsmentioning
confidence: 99%
“…The source function was recently developed by Gatti and Bader [8] and successfully supported other investigations [30,31].…”
Section: Geometry Of the Rahb And Topological Parametersmentioning
confidence: 99%